The Results of Developing the Competence in Creating Digital Learning Media Using Artificial Intelligence (AI) Tools of Basic Education Teachers with Design Thinking Process - ศักดิ์บุญญารัตน์ ธัญญพัทธ์; เทศปลื้ม มาริษา; บุญมา ซิธิวาโวร์; ชาวระนอง ชัยยศ; มาตรพรหม ลือศักดิ์ มาตรพรหม (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to: (1) enhance the competency of basic education teachers in creating digital learning media using Artificial Intelligence (AI) tools through the design thinking process; and (2) propose guidelines for the development of this competency. A mixed-methods research approach was employed. The study’s target group comprised 60 basic education teachers recruited through voluntary sampling. Research instruments included: (1) a training activity plan based on the design thinking process; (2) a competency assessment form for digital learning media creation; and (3) a focus group discussion protocol. Quantitative data were analyzed using mean, and percentage calculations, while qualitative data were examined through content analysis. The research findings indicated that: (1) teachers who participated in training utilizing the design thinking process exhibited a good level of competency in creating digital learning media with AI tools, achieving an average competency level of 80.11 percent; and (2) the teachers proposed guidelines to further develop their competency in digital learning media creation with AI tools. These guidelines include the establishment of a professional learning community for teachers to exchange knowledge on using AI tools within the design thinking framework. Additionally, they recommended compiling examples of application usage and troubleshooting methods for various web applications to address challenges encountered during the development of digital learning media. A key finding of this study is that, with appropriate guidance and tools, educators can effectively keep pace with technological advancements and leverage AI to develop learning materials and educational innovations tailored to the school context. This reflects a novel perspective that expands the scope of teacher development in the digital age.